2022
DOI: 10.21037/atm-21-4988
|View full text |Cite
|
Sign up to set email alerts
|

Preemptive analgesia in the “non-tube no fasting” fast track program for resectable esophageal carcinoma

Abstract: China has the highest incidence of esophageal squamous cell carcinoma in the world. The 2020 global cancer burden data released by the International Agency for Research on Cancer of the World Health Organization showed that esophageal carcinoma ranks sixth in incidence [324,000] and fourth in mortality among malignant tumors in China, accounting for 7.1% and 10% of the total number of new cancers and cancer deaths, respectively. The global 5-year survival rate of esophageal carcinoma is 15-25%. It is the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Despite improved perioperative management, the morbidity and mortality rates are still the highest after esophagectomy among all solid tumor surgeries. MIE involves dissection and trauma to large muscles, postoperative pain after MIE is still common and is a major factor affecting patients' recovery [15]. Adequate pain control can decrease PPCs, such as atelectasis or pneumonia and improve the quality of life for thoracic patients[16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite improved perioperative management, the morbidity and mortality rates are still the highest after esophagectomy among all solid tumor surgeries. MIE involves dissection and trauma to large muscles, postoperative pain after MIE is still common and is a major factor affecting patients' recovery [15]. Adequate pain control can decrease PPCs, such as atelectasis or pneumonia and improve the quality of life for thoracic patients[16].…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al reported that continuous paravertebral block alleviated the pain of patients in the resting and active state for patients undergoing MIE, which enabled patients to get out of bed early, cough and sputum effectively, and decreased the incidence of pulmonary complications [7]. Postoperative pain in MIE mainly comes from the trauma of thoracic and abdomen, especially originated from the upper abdominal incision [15]. So, we applied SAPB for thoracic analgesia and used TAPB combined with RSB for abdominal analgesia.…”
Section: Discussionmentioning
confidence: 99%